2020
DOI: 10.1124/mol.120.119693
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA hsa-miR-1301-3p Regulates Human ADH6, ALDH5A1 and ALDH8A1 in the Ethanol-Acetaldehyde-Acetate Metabolic Pathway

Abstract: Alcohol dehydrogenases (ADHs) and aldehyde dehydrogenases (ALDHs) are vital enzymes involved in the metabolism of a variety of alcohols. Differences in the expression and enzymatic activity of human ADHs and ALDHs correlate with individual variability in metabolizing alcohols and drugs and in the susceptibility to alcoholic liver disease. MicroRNAs (miRNAs) function as epigenetic modulators to regulate the expression of drug-metabolizing enzymes. To characterize miRNAs that target ADHs and ALDHs in human liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
(60 reference statements)
0
6
1
Order By: Relevance
“…Regarding miRNAs regulating ADH1B expression, to the best of our knowledge so far, no reports are available in the literature. In human hepatoma cells, expression of ADH6 is reportedly suppressed by miR-1301-3p [13], while expression of ADH4 was increased by miR-148a-3p [14]. However, serum levels of miR-1301-3p and miR-148a-3p in the subjects of this study were too low for a comparison between Austrian and Japanese men.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Regarding miRNAs regulating ADH1B expression, to the best of our knowledge so far, no reports are available in the literature. In human hepatoma cells, expression of ADH6 is reportedly suppressed by miR-1301-3p [13], while expression of ADH4 was increased by miR-148a-3p [14]. However, serum levels of miR-1301-3p and miR-148a-3p in the subjects of this study were too low for a comparison between Austrian and Japanese men.…”
Section: Discussioncontrasting
confidence: 60%
“…Collectively, these findings suggest that miRNAs play an important role in the regulation of ALDH2 expression in several species. On the other hand, there are only two reports on regulation of alcohol dehydrogenase (ADH) by miRNA: in human hepatoma cells, miR-1301-3p suppressed expression of ADH6 [13], while miR-148a-3p promoted ADH4 expression [14]. To the best of our knowledge, there have been no reports on miRNAs that regulate expression of ADH1B.…”
Section: Introductionmentioning
confidence: 99%
“…ALDHs and other enzymes in this group are poorly biochemically studied dehydrogenases that use retinoic acid, gamma-aminobutyric acid, or betaine as a cosubstrate (47,48). Interestingly, ALDH8A1 expression was shown to be induced by ethanol in the liver, and this enzyme catalyzes the reaction of 2-aminomuconate semialdehyde and NAD + to produce 2-aminomuconate and NADH in the kynurenine pathway of tryptophan catabolism (49,50). In summary, our RNA-Seq experiments identified genes that are impacted by the NADH reductive stress induced by the novel genetically encoded tool, Ec STH.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, studies have shown that the down-regulation of miR-1301 is associated with the malignant clinical features and poor OS of patients with colorectal cancer (50), and the overexpression of miR-1301 has been shown to inhibit cell proliferation, migration and invasion (51). It is worth noting that miR-1301-3p has been widely studied in liver cancer, breast cancer and other cancer types for its anti-tumor effect (52)(53)(54)(55). Regarding miR-3655, wu et al showed that miR-3655 down-regulates CXCL5 and is used as a new diagnostic and prognostic marker for osteosarcoma (56).…”
Section: Discussionmentioning
confidence: 99%